Prevention and Control of Selected Chronic NCDs in Sri Lanka : Policy Options and Action - Engelgau, Michael; Okamoto, Kyoko; Navaratne, Kumari Vinodhani; Gopalan, Sundararajan (World Bank, Washington, DC, 2013)
Strategic decisions to reorient population-based prevention and clinic- and hospital-based care policies toward non-communicable diseases (NCDs) will enable healthier aging and reduce loss of productivity among the working-age population in Sri Lanka. This report aims to stimulate policy dialogue for NCDs and to provide an evidence base to facilitate decisions. Its focus is mainly on chronic NCDs-that is, cardiovascular disease (CVD), diabetes, and asthma/chronic obstructive pulmonary disease (COPD), and to a lesser extent cancer-and their major modifiable risk factors (tobacco use, unhealthy diet, lack of exercise, and harmful alcohol use). This is not to detract, though, from the importance of injuries and mental health since both are major issues that carry a huge burden, as supported by evidence in this report. Several major areas for policies and actions emerged from the analysis of Sri Lanka's health sector organization and capacity as well as its NCD orientation. Some areas are not specific to NCDs but, rather, will strengthen the health sector generally while leading to better NCD prevention and control. These areas include: (i) increasing financial resources for NCD prevention and control, (ii) increasing access to NCD drugs, especially for the poor, (iii) addressing social determinants, (iv) focusing on specific NCDs, (v) addressing under nutrition and over nutrition, (vi) creating an intensified national NCD program, strengthening and reorganizing NCD prevention and curative care services, (vii) moving services closer to clients and improving efficiency, (viii) further decentralizing and devolving health service delivery, (ix) human resource development for NCD prevention and control, (x) creating a national NCD surveillance system, and (xi) developing public-private partnerships and aligning service delivery.